2020
DOI: 10.21608/ejm.2020.20200.1135
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antibacterial Activity of some Indian and Yemeni Honey against few Bacterial Isolates from Human Patients

Abstract: T HE PRESENT study is aimed to evaluate the antibacterial effect of four types of Indian and Yemeni honey at 80% and 50% w/v concentrations against different pathogens including Methicillin-Resistant Staphylococcus aureus (MRSA), Methicillin-Sensitive Staphylococcus aureus (MSSA), Escherichia coli, and Pseudomonas aeruginosa. Agar well diffusion method, minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) values were used in this evaluation. All the examined honey samples recorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…The inhibition zone diameters of SH and MH were 16.33 ± 0.33 mm and 16.66 ± 1.20 mm, respectively, similar to the positive control (gentamicin 16.5 ± 0.40 mm). Our findings agree with a study conducted by Saeed and Jayashankar [ 20 ], who tested SH against clinically isolated E. coli at a concentration of 80% (1300 mg/disc). On the contrary, SH in that study showed some antibacterial activity against the other clinical isolated bacterial strains, including MSSA (15 ± 0.08 mm), Pseudomonas aeruginosa (14 ± 0.15 mm) and methicillin-resistant Staphylococcus aureus (MRSA) (16 ± 0.45 mm).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The inhibition zone diameters of SH and MH were 16.33 ± 0.33 mm and 16.66 ± 1.20 mm, respectively, similar to the positive control (gentamicin 16.5 ± 0.40 mm). Our findings agree with a study conducted by Saeed and Jayashankar [ 20 ], who tested SH against clinically isolated E. coli at a concentration of 80% (1300 mg/disc). On the contrary, SH in that study showed some antibacterial activity against the other clinical isolated bacterial strains, including MSSA (15 ± 0.08 mm), Pseudomonas aeruginosa (14 ± 0.15 mm) and methicillin-resistant Staphylococcus aureus (MRSA) (16 ± 0.45 mm).…”
Section: Discussionsupporting
confidence: 93%
“…Our results revealed that both MIC and MBC were the same; SH was 50%, and MH was 30%. A previous study conducted against a clinical isolate of E. coli and SH showed a different result in which the MIC was 10 %, while MBC was 40% [ 20 ]. The MIC result obtained from [ 3 ] of SH against E. coli was 40%, whereas MBC was 60%.…”
Section: Discussionmentioning
confidence: 99%
“…The range of the pH value in honey sample studied was higher than that obtained in Ethiopian honey (3.40-4.65) [15], in the eastern Moroccan honey (3.53-4.94) [18], in Algerian honey (3.70-4.00) [23] and in honeys available in Mexican market (3.71-4.21) [11]. It's also higher than the results previously in Sidr Dowany and Somer Shabowah Yemeni honey which was 4.5 and 5.2 respectively [17].…”
Section: Phmentioning
confidence: 92%
“…The results in table 1 shows that moisture content was 18.63±1.39% and ranged between 16-19.5% in Yemeni honey samples included in this study. These results are fallen in the range of Ethiopian honey (17.56-22.57%) [15], Yemeni honey (13.5-19.5%) [17] and the eastern Moroccan honey (15.39-19.37%) [18] but the moisture content was higher than the moisture contents of Nigerian honey which had average value (16.00±2.19 g/100 g) [14]. The moisture contents in monoflora honeys from Andean Region of Ecuador was 16.42±2.53, 18.62±1.84 and 14.63±2.74 in Avocado, Eucalyptus and Rapeseed honeys respectively [19].…”
Section: Moisture Contentmentioning
confidence: 99%
See 1 more Smart Citation